De Sitter vacua — when are ‘subleading corrections’ really subleading? - Ivonne Zavala Carrasco (Journal of High Energy Physics, 2023)
We consider various string-loop, warping and curvature corrections that are expected to appear in type IIB moduli stabilisation scenarios. It has recently been argued, in the context of strongly-warped LVS de Sitter vacua, that it is impossible to achieve parametric suppression in all of these corrections simultaneously [1]. We investigate corrections in the context of the recently discovered weakly-warped LVS de Sitter vacua, which represent a distinct branch of solutions in type IIB flux compactifications. The weakly-warped solution is supported by small conifold flux numbers MK ≲ 32, but still requires a large flux contribution to the D3-tadpole, now from the bulk. Warping corrections become less problematic, and some corrections even help to reach the weakly-warped regime of parameter space. Other corrections continue to be dangerous and would require numerical coefficients to be computed — and found to be small — in order not to destroy the consistency of the weakly-warped LVS de Sitter solution. We motivate why this may be possible.